Norwegian Seismic Array (NORSAR). - Bungum,H. (1974)
The reports on surface wave studies include one describing a recently initiated study of source mechanisms for North Atlantic earthquakes. Work on actual explosion data includes one report on non-linear instrumental response to strong long period P-waves, and one describing the continued work on m sub b:M sub s at NORSAR. Also, a comment on the effect of multipathing on single station group velocity analysis is given.